O-008 Functional As Opposed To Anatomical Characterization Of The Middle Cerebral Artery "M2" Divisions Can Expand The Category Of Large Vessel Occlusions Amenable For Stroke Interventions. (29th July 2016) - Rai, A; Tarabishy, A; Link, P; Boo, S; Lucke-Wold, N; Domico, J; Carpenter, J
Abstract : Background: M2 occlusions have typically been excluded from endovascular stroke trials. However variations in the size of the MCA branches and the area of brain they supply runs the risk of excluding a dominant trunk supplying a large part of the brain and hence resulting in a significant ischemic injury. Perfusion imaging allows a more functional depiction of the vascular territory and maybe more relevant for endovascular selection. Objective: To determine the rate of M2 occlusions amongst all hospital discharges for acute ischemic stroke (AIS) and to functionally classify occlusion severity based on baseline perfusion imaging and final infarct volume. To secondarily extrapolate this rate to the national inpatient sample (NIS) database for estimating the annual burden of M2 occlusions that may benefit from endovascular therapy. Methodology: All hospital discharges for AIS (ICD-9 codes 433.xx, 434.xx 435.xx) over a 3 year period from a large rural hospital system were screened for an M2 occlusion based on admission imaging. These were classified into the superior or inferior trunk based on anatomy and dominant or non-dominant division based on size. The occlusion severity was graded on time-to-peak (TTP) perfusion imaging as a proportion of the entire MCA. Infarct volume on follow up imaging represented the final ischemic injury. The results were extrapolated to the NIS-database. Results: Out of 2757 AIS hospital discharges 118 (4.3%) patients were identified with an M2 occlusion. 71 (60.2%) of these patients presented within 6 hours and 47 (39.8%) after 6 hours of last seen normal (LSN). Baseline perfusion (TTP) and follow-up imaging was available for 75 patients. The superior trunk (ST) was involved in 36 (48%) and the inferior trunk (IT) in 39 (52%) patients. In 27 (75%) patients with ST involvement, it was the dominant division versus 36 (92.3%) patients with IT occlusion had it as the dominant division (p = 0.037). Overall a dominant division was occluded in 63 (84%) patients and a non-dominant in 12 (16%) patients. In 47 (74.6%) patients with a dominant branch occlusion (ST or IT) the TTP abnormality was >1/3 rd of the MCA distribution versus 5 (41.7%) patients with a non-dominant branch occlusion that had >1/3 rd MCA involvement (p = 0.02). Patients with a dominant branch occlusion had a final infarct volume of 49.6 cm 2 (±46.3) versus a volume of 16.7 cm 2 (±13.8) for non-dominant occlusions (p = 0.009). In patients with >1/3 rd MCA involvement on TTP images the infarct volume was 51.5 cm 2 (±47.6) versus an infarct volume of 28.1 cm 2 (±31.5) in patients with ≤1/3 rd MCA abnormality (p = 0.03). There were 1, 135, 030 AIS discharges nationally for 2013 for the same ICD-9 codes. A 4% rate of M2 occlusions yields 45, 401 potential patients with an M2 occlusion of which 38, 137 can have a dominant branch involvement and hence the risk of significant ischemic injury. Conclusion: Patients with a dominant branch occlusion, whether superior or inferior, had larger TTP abnormalities (>1/3 rd MCA) and final infarct volumes. An estimated 37, 137 AIS patients can have a dominant M2 occlusion with significant risk of ischemic injury. A functional as opposed to pure anatomical classification may allow selecting these patients for endovascular therapy. Disclosures: A. Rai: 1; C; Stryker Neurovascular. 2; C; Stryker Neurovascular. A. Tarabishy: None. P. Link: None. S. Boo: None. N. Lucke-Wold: None. J. Domico: None. J. Carpenter: None.